2021
DOI: 10.1088/1361-6528/ac2763
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of well-ordered PbS nanowires in aluminum oxide template by sulfurization and vacuum injection molding processes

Abstract: Lead (Pb) nanowire arrays were fabricated with anodic aluminum oxide (AAO) templates of 30, 100 and 300 nm in pore diameters. Through vacuum injection molding process, Pb/AAO composite was obtained, and lead sulfide (PbS) could further be synthesized after exposing to sulfur gas. AAO templates with different pore sizes were fabricated by using pure aluminum in a two-step anodization. Three types of solutions, which are 10 vol% sulfuric acid, 3 wt% oxalic acid and 1 vol% phosphoric acid, were adopted to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Masuda et al, in 1995 [74], proposed the two-step anodization method for AAO technology, as shown in Figure 7, which laid the foundation for the AAO processes and applications. Many groups still follow this approach [128][129][130][131] today for AAO-related research. The first AAO can leave a pre-pattern after the removal process, making the hexagonal structure more regular during the second step of anodization.…”
Section: Conventional Two-step Processmentioning
confidence: 99%
“…Masuda et al, in 1995 [74], proposed the two-step anodization method for AAO technology, as shown in Figure 7, which laid the foundation for the AAO processes and applications. Many groups still follow this approach [128][129][130][131] today for AAO-related research. The first AAO can leave a pre-pattern after the removal process, making the hexagonal structure more regular during the second step of anodization.…”
Section: Conventional Two-step Processmentioning
confidence: 99%
“…Nanowires are a class of nanostructures that have been widely fabricated using AAO [241,[251][252][253]. The typical process flow for nanowire synthesis using this technique involves the fabrication of AAO templates with various pore sizes and geometries followed by the production and deposition of the starting materials for the nanowires (e.g.…”
Section: 31mentioning
confidence: 99%